Perceived social support and depressive symptoms among vocational college students: the serial mediating roles of positive coping and post-stress growth - Lu, Wenfang; Ouyang, Mingkun; Huang, Xiaoyu (Frontiers in Psychology, 2026)
Vocational college students face heightened depression risks due to unique psychosocial stressors, yet mechanisms linking perceived social support to depression mitigation remain inadequately explored. This cross-sectional study investigated the serial mediating roles of positive coping strategies and post-stress growth in 960 Chinese vocational students using validated scales (perceived social support scale, simplified coping style questionnaire, post-stress growth inventory, self-rating depression scale) analyzed via Hayes’ PROCESS Model 6. Results demonstrated that perceived social support significantly reduced depressive symptoms through three pathways: direct effects, independent mediation via positive coping strategies, independent mediation through post-stress growth, and sequential mediation where support enhanced coping strategies that subsequently fostered post-stress growth and reduced depression. Collectively, these adaptive psychological processes accounted for the majority of the total protective effect. Findings underscore the value of multipathway campus interventions targeting social support networks, cognitive-behavioral coping training, and growth-focused resilience programs to address mental health disparities in vocational education populations.